PARTICIPATION OF WOMEN OF SUNDARBANS IN FISHERIES DECISION MAKING - ROY, APARNA; BHAUMIK, UTPAL (Journal of the Inland Fisheries Society of India, 2021)
A study was conducted in Fraserganj area of Sundarban to assess the extent of rural women participation in decision making process related to fisheries. Highest participation of women in decision making was on the matter related to preparation of food items (67%) and giving child supplementary food items (67%). Based on the study several measures have been suggested to improve womans’ decision making capacity.Key words: Women, decision making, participation